Peningkatan Kapasitas Sumber Daya Manusia Melalui Pembangunan Inklusif Dalam Mendukung Desa Wisata Budaya Di Desa Plunturan - Anggraeny Puspaningtyas (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
Plunturan Village is one of the villages located in Ponorogo Regency which has many cultural products and is still preserved. One of the cultural products of the village is Reog Ki Onggo Pati. Reog Ki Onggo Pati is an art that has become an icon of Plunturan Village because it still upholds the originality of Reyog. The purpose of this study is to analyze the capacity building of human resources (HR) through inclusive development in supporting the Cultural Tourism Village in Plunturan Village, Pulung District, Ponorogo Regency, East Java. The researcher uses a qualitative research type with a descriptive approach. The research focus which is the limitation of the research is the result of several literature studies that are in accordance with the existing conditions of Plunturan Village, namely a) resources for development; b) decent employment; c) strong and sustainable economic growth, and d) rising standards of living. Based on the results of research and discussions conducted by researchers, it can be concluded that efforts to develop human resource capacity through inclusive growth in supporting the Cultural Tourism Village in Plunturan Village have been running but are still very slow. Resources for the development of Plunturan Tourism Village are not ready in all aspects. If the resources are strong, then the ongoing economic growth will be sustainable so as to create long-term redistribution. Meanwhile, viewed from the employment aspect, the Village Government, BUMDes and Pokdarwis and other village government institutions have not coordinated well within the scope of the development of Plunturan Tourism Village so that economic growth in the village is very slow. This results in weak competitiveness between villages and/or regions in terms of cultural tourism. If these aspects are implemented and coordinated properly, the output will be able to improve the living standards of Plunturan Village.